Antiglucocorticoid activity of hepatocyte nuclear factor-6 - Pierreux, Christophe E. (The National Academy of Sciences, 1999)
Glucocorticoids exert their effects on gene transcription through ubiquitous receptors that bind to regulatory sequences present in many genes. These glucocorticoid receptors are present in all cell types, yet glucocorticoid action is controlled in a tissue-specific way. One mechanism for this control relies on tissue-specific transcriptional activators that bind in the vicinity of the glucocorticoid receptor and are required for receptor action. We now describe a gene-specific and tissue-specific inhibitory mechanism through which glucocorticoid action is repressed by a tissue-restricted transcription factor, hepatocyte nuclear factor-6 (HNF-6). HNF-6 inhibits the glucocorticoid-induced stimulation of two genes coding for enzymes of liver glucose metabolism, namely 6-phosphofructo-2-kinase and phosphoenolpyruvate carboxykinase. Binding of HNF-6 to DNA is required for inhibition of glucocorticoid receptor activity. In vitro and in vivo experiments suggest that this inhibition is mediated by a direct HNF-6/glucocorticoid receptor interaction involving the amino-terminal domain of HNF-6 and the DNA-binding domain of the receptor. Thus, in addition to its known property of stimulating transcription of liver-expressed genes, HNF-6 can antagonize glucocorticoid-stimulated gene transcription.